Fulfilment efficiency, AI capability, and cross-border e-commerce development in China: complementarities, regional heterogeneity, and resource-saving potential - Luo, Hongen; Kamarudin, Fakarudin; Soh, Weini; Shan, Zheng (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
China’s cross-border e-commerce (CBEC) has expanded rapidly, yet province-level evidence remains limited on how AI development conditions the contribution of logistics fulfilment efficiency (LEF) to cross-border e-commerce development (CBED), especially across regions with uneven digital maturity. This study tests whether AI capability amplifies the marginal effect of logistics fulfilment efficiency (LEF) for CBED and whether this complementarity varies across eastern, central, and western China. Using a balanced panel of thirty-one provinces over 2017–2023 (N = 217), we combine a Super-SBM DEA logistics fulfilment efficiency measure (LEF), a four-pillar AI Development Index (AIDI), and customs-based CBED indicators. Two-step System GMM models are estimated for the full sample and regional subsamples to account for dynamic persistence and endogeneity concerns. Results indicate that higher LEF is associated with higher CBED and that AIDI strengthens this relationship via the interaction term; the complementarity is the largest in eastern provinces and remains positive but smaller in central and western regions. Overall, the evidence suggests that logistics fulfilment efficiency and AI capability act as complementary enablers of cross-border e-commerce development, supporting provincial competitiveness as CBEC scales. Sustainability implications are therefore discussed via operational-efficiency channels rather than direct environmental outcomes.